(untitled) (Research, Society and Development, 2021)
Introduction: Changes in the tear through and infraorbital region are one of the first recognizable signs of aging. These are common complaints in aesthetic medicine and there are many treatment options available. With this in mind, the purpose of this study is to perform a literature review to describe the anatomy and changes in the infraorbital region due to aging and present the main therapeutic options for each case. Materials and methods: A simple literature review was performed in the databases: Pubmed, Scielo, Web of Sciences, using the descriptors: Tear trough, Infraorbital, Dark-circles, Lower-Eyelid, Hyperpigmentation and Midface, treatment, therapeutics with their corresponding terms in English and Portuguese. Results: Fillers, collagen biostimulators, lasers, radiofrequency devices, microagulants, chemical peels, cosmeceuticals and botulinum toxin are available non-surgical treatment options discussed in the literature, it was found to significantly improve and rejuvenate the infraorbital region. Conclusion: A thorough understanding of the anatomy and changes that occur with aging are of utmost importance in evaluating the infraorbital region to determine appropriate treatment options as a way to achieve optimal rejuvenation.